Development of Bioenergy Technologies in Uganda: A Review of Progress - Okello, Collins; Faugno, Salvatore (Renewable and Sustainable Energy Reviews, 2013)
Biomass is a renewable energy resource; however, its exploitation raises concerns about its ability to sustain the growing demand and its negative impacts on the environment, particularly in developing countries. These concerns are more prominent on the African continent where high population growth rates is leading to high rates of deforestation due to expansion of agricultural land and increased demand for bioenergy. Use of traditional and inefficient bioenergy technologies and appliances also exacerbate the problem. This paper presents a review of the efforts and progress made by different organisations in promoting improved bioenergy technologies in Uganda. The study was based on an extensive review of available literature on improved bioenergy technologies introduced in the country. It was found that there is high level of wastage of biomass resources since an estimated 72.7% of the population use traditional cooking stoves with efficiency estimated to be less than 10%. Inefficient cooking stoves are also blamed for indoor air pollution and respiratory illness reported amongst its users. Modern bioenergy technologies such as biomass gasification, cogeneration, biogas generation, biomass densification, and energy-efficient cooking stoves have been introduced in the country but have certainly not been widely disseminated. The country should pursue policies that will accelerate proliferation of more efficient bioenergy technologies in order to reduce the negative environmental impacts of bioenergy utilisation and to ensure sustainability of biomass supplies.
Keywords: Bioenergy technologies; Biogas; Gasification; Densification; Uganda